Cancers in Australia in 2010 attributable to infectious agents. (October 2015) - Antonsson, Annika; Wilson, Louise F.; Kendall, Bradley J.; Bain, Christopher J.; Whiteman, David C.; Neale, Rachel E.
Abstract Objectives: To estimate the proportion and numbers of cancers in Australia in 2010 attributable to infectious agents. Methods: The population attributable fraction (PAF) and number of cancers caused by hepatitis B and C viruses (HBV, HCV), Helicobacter pylori and human immunodeficiency virus (HIV) were calculated using standard formulae incorporating prevalence of infection in the Australian population, the relative risks associated with that infection and cancer incidence. For cancers with very strong associations to the infectious agent (Epstein‐Barr virus [EBV], human papillomavirus [HPV] and HIV/Kaposi's sarcoma herpes virus [KSHV]), calculations were based on viral prevalence in the tumour. Results: An estimated 3, 421 cancers (2.9% of all cancers) in Australia in 2010 were attributable to infections. Infectious agents causing the largest numbers of cancers were HPV (n=1, 706), H. pylori (n=793) and HBV/HCV (n=518). Cancer sites with the greatest number of cancers caused by infections were cervix (n=818), stomach (n=694) and liver (n=483). Cancers with highest proportions attributable to infectious agents were Kaposi's sarcoma (100%), cervix (100%), nasopharynx (87%), anus (84%) and vagina (70%). Conclusions: Infectious agents cause more than 3, 000 cancers annually in Australia. Implications: Opportunities for cancer prevention through infection control are considerable, even in a 'first world' nation like Australia.